EFFECT OF STIMULATORS AND PROTECTIVE TOOLS ON THE COLLECTION INDICATORS IN WHEAT PLANTS (Field experiment results as of February 16, 2024) - Q. Davronov; Z. Sadikova (Web of Journals Publishing, 2026)
This study investigated the effect of various biostimulants, fungicides, insecticides, and humic fertilizers on the tillering capacity of wheat at the early stages of growth. Experiments were conducted across 11 variants with three repetitions each, and the number of seedlings and tillers were recorded for each variant. Based on the average values, the most effective treatment combinations were identified. The results have practical significance for selecting optimal treatments and scientifically substantiating agronomic practices aimed at increasing wheat productivity.
Keywords: Wheat (Triticum aestivum L.), field experiment, tillering, seedling density, biostimulant, humic substances, potassium humate, phytohormone, fungicide, insecticide, Novogumin, Impakt, Karat, integrated treatment, early growth stage, productivity.